Noninvasive Detection of Activating Estrogen Receptor 1 (ESR1) Mutations in Estrogen Receptor–Positive Metastatic Breast Cancer. (6th January 2020) - Guttery, David S; Page, Karen; Hills, Allison; Woodley, Laura; Marchese, Stephanie D; Rghebi, Basma; Hastings, Robert K; Luo, Jinli; Pringle, J Howard; Stebbing, Justin; Coombes, R Charles; Ali, Simak; et al.
Abstract: BACKGROUND: Activating mutations in the estrogen receptor 1 ( ESR1 ) gene are acquired on treatment and can drive resistance to endocrine therapy. Because of the spatial and temporal limitations of needle core biopsies, our goal was to develop a highly sensitive, less invasive method of detecting activating ESR1 mutations via circulating cell-free DNA (cfDNA) and tumor cells as a "liquid biopsy." METHODS: We developed a targeted 23-amplicon next-generation sequencing (NGS) panel for detection of hot-spot mutations in ESR1, phosphatidylinositol-4, 5-bisphosphate 3-kinase, catalytic subunit alpha ( PIK3CA ), tumor protein p53 ( TP53 ), fibroblast growth factor receptor 1 ( FGFR1 ), and fibroblast growth factor receptor 2 ( FGFR2 ) in 48 patients with estrogen receptor-α–positive metastatic breast cancer who were receiving systemic therapy. Selected mutations were validated using droplet digital PCR (ddPCR). RESULTS: Nine baseline cfDNA samples had an ESR1 mutation. NGS detected 3 activating mutations in ESR1, and 3 hot-spot mutations in PIK3CA, and 3 in TP53 in baseline cfDNA, and the ESR1 p.D538G mutation in 1 matched circulating tumor cell sample. ddPCR analysis was more sensitive than NGS and identified 6 additional baseline cfDNA samples with the ESR1 p.D538G mutation at a frequency of <1%. In serial blood samples from 11 patients, 4 showed changes in cfDNA, 2 with emergence of a mutation in ESR1. We also detected a low frequency ESR1 mutation (1.3%) in cfDNA of 1 primary patient who was thought to have metastatic disease but was clear by scans. CONCLUSIONS: Early identification of ESR1 mutations by liquid biopsy might allow for cessation of ineffective endocrine therapies and switching to other treatments, without the need for tissue biopsy and before the emergence of metastatic disease.